1974
DOI: 10.1143/ptps.55.284
|View full text |Cite
|
Sign up to set email alerts
|

B. Initial Value Problems of One-Dimensional Self-Modulation of Nonlinear Waves in Dispersive Media

Abstract: We propose a novel Er-doped fiber laser with an adjustable output pulse. The optical system is composed of an integrated optic circuit of LiNbO, waveguide, a Sagnac fiber loop, and an Er-doped fiber. A simple analysis is presented and a related experiment is conducted. Our result shows that when the mode lock occuls both the pulse width and the pulse repetition can be simply adjusted by the amplitude of the phase modulation signal. In addition, this fiber laser can generate an output with unequal separations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
448
1
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 819 publications
(475 citation statements)
references
References 0 publications
21
448
1
5
Order By: Relevance
“…The class of Tovbis-Venakides potentials (see (8)) involves a parameter µ ∈ R (µ = 0 is the special case studied earlier by Satsuma and Yajima [19]). In fact, we chose to use the symbol µ for the parameter in (2) precisely because this parameter plays a similar role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The class of Tovbis-Venakides potentials (see (8)) involves a parameter µ ∈ R (µ = 0 is the special case studied earlier by Satsuma and Yajima [19]). In fact, we chose to use the symbol µ for the parameter in (2) precisely because this parameter plays a similar role.…”
Section: Discussionmentioning
confidence: 99%
“…Satsuma and Yajima [19] found that with initial data q(x, 0; N )=N sech(x) the scattering data relevant for the focusing NLS equation can be found in closed form for any N ∈ R. Furthermore, if N ∈ Z then the scattering data are reflectionless and so the solution q(x, t; N ) can be found more-or-less explicitly. In [17] it was noted that, with ε = c/N and τ = N t/c, the function φ(x, τ ; ε) = cq(x, t; N )/N satisfies the initial-value problem (7) iεφ τ + ε 2 2 φ xx + |φ| 2 φ = 0, φ(x, 0; ε) = c sech(x).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single-and manysoliton solutions to this equation have been extensively explored in the context of optical solitons [50][51][52][53][54][55]. We review the results pertinent to soliton dynamics in this section.…”
Section: Dynamics and Collisions Of The Classic Bright Solitonmentioning
confidence: 99%
“…The majority of these dynamics can be understood on the basis of a simple particle model. The interaction of solitons with radiation is more mathematically involved [52,55,75] and no similarly general picture is available. In the absence of radiation, the dynamics of multiple bright solitons are dominated by the interactions and collisions between solitons.…”
Section: Bright Soliton Dynamics and Collisionsmentioning
confidence: 99%